PENGAWASAN KINERJA PEGAWAI PADA KANTOR CAMAT BUKIT RAYA KOTA PEKANBARU - Ivan Afwan; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Head Office is one of the government agencies that regulate a variety of public interests, including the maintenance of identity cards, processing of land documents, handling letters of building permits, in addition to the Head is also in charge of monitoring the performance of employees where a government is sought for the implementation of work processes can be efficiently and effectively.However, problems occurred that oversight has not been done effectively, which can be seen not timely implementation of control, causing delays in the work. Can be formulated that control how the performance of the Head Office Bukit Raya Pekanbaru. The aim of this study was to determine how the Employee Performance Monitoring at Head Office Bukit Raya Pekanbaru.To analyze these problems the author uses the theory Brantas. This research is a descriptive qualitative approach, where data collection techniques are observation and interviews with key informants as key informants and snowball sampling in the determination of supplementary information.Conclusion derived from the results of the study showed that the Monitoring Employee Performance At Head Office Bukit Raya less effectively. Any work performed by an employee are in accordance with the basic tasks and functions. In the execution of this task, the boss gave full credence to subordinates to carry out each task each work performed by employees in the event of deviation from a work supervisor just give warning without the realization of such admonition. So that supervision can improve employee performance let can give guidance / instructions clear to employees about the various procedures of work, and provide sanctions against employees who commit irregularities within a job.Keywords : Monitoring, Performance, Employee